2021
DOI: 10.21079/11681/42180
|View full text |Cite
|
Sign up to set email alerts
|

Thermal camera reliability study : FLIR Pro One

Abstract: The purpose of the effort described herein is to verify the reliability of the FLIR One Pro Gen 3 (FLIR One) unit through systematic experiments that compare the temperature perceived by the unit to the temperature measured by contact sensors on different materials through a range of temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In addition to the use of the fiber optic, the authors positioned a FLIR One Pro thermographic camera facing the back of the plate [24]. Previous studies [7] have shown good correlation between the use of commercial off-the-shelf inexpensive cameras and VrWeld predicted results.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In addition to the use of the fiber optic, the authors positioned a FLIR One Pro thermographic camera facing the back of the plate [24]. Previous studies [7] have shown good correlation between the use of commercial off-the-shelf inexpensive cameras and VrWeld predicted results.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Since fever is a common symptom of COVID-19, several studies have highlighted the use of thermal cameras for fever screening to minimize travelers with high body temperatures [16]. Even when other influenza-type epidemics, such as SARS and MERS were spreading, body temperature regulation was already a standard technique [17]- [19]. Thermal imaging or infrared thermography is a technology used to measure or "see" infrared, the wavelengths emitted from objects, and then convert the temperature information into an image [19].…”
Section: Introductionmentioning
confidence: 99%
“…The images can be considered as an averaged representation of the S Oss air jet. To illustrate the effectiveness of this technique, we show some pictures taken with a FLIR One camera connected to a smartphone [4]. The hair dryer operated at intermediate air speed/temperature (precise values were not influential in this experiment).…”
mentioning
confidence: 99%